Sexually transmitted diseases and HIV-1 infection among homosexual men in England and Wales. Issue 6875 (13th February 1993) - Evans, B G; Catchpole, M A; Heptonstall, J; Mortimer, J Y; McCarrigle, C A; Nicoll, A G; Waight, P; Gill, O N; Swan, A V
Abstract : OBJECTIVE--To examine surveillance data for evidence of changing sexual behaviour and continuing transmission of HIV-1 among men who have sex with men. DESIGN--Analytic study of surveillance data on sexually transmitted diseases. SETTING--England and Wales. MAIN OUTCOME MEASURES--Number of cases of rectal gonorrhoea and newly diagnosed HIV infection in homosexual men. RESULTS--New cases of gonorrhoea among men attending genitourinary medicine clinics increased by 7.7% in 1989 and by 4.2% in 1990. Reports of rectal isolates of Neisseria gonorrhoeae also rose and the male to female ratio for patients with rectal gonorrhoea changed from 0.3:1 during 1988-9 to 2.6:1 in 1990-1. Although the overall number of cases of acute hepatitis B fell during 1988-91, 81 and 82 homosexual men were infected in 1990 and 1991 respectively compared with 50 and 42 in 1988 and 1989. 1526 men had HIV-1 infection diagnosed in 1991, the largest number since 1987. Twenty eight of the 97 (29%) men who seroconverted between January 1989 and December 1991 were aged less than 25. The proportion of men aged 15-19 who were found to be infected with HIV-1 at their first test increased from an average of 2.4% up to 1990 to 4.7% in the first nine months of 1991. The prevalence of HIV infection in men under 25 attending genitourinary medicine clinics in London was 17% compared with 7.8% outside London. CONCLUSION--Unsafe sexual behaviour and HIV transmissions have increased among homosexual men after a period of decline. Recent HIV transmissions may disproportionately affect younger men.